INNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION FAÇADE FOR AN ENERGY PERFORMANCE AND THERMAL NNOVATION - (:unkn) unknown (university of eloued جامعة الوادي, 2020)
This paper discusse This paper discusse This paper discusse This paper discusse This paper discusse s the e s the es the e s the es the energy innovation of external fac nergy innovation of external facnergy innovation of external fac nergy innovation of external fac nergy innovation of external fac nergy innovation of external facnergy innovation of external fac nergy innovation of external facnergy innovation of external facnergy innovation of external fac nergy innovation of external fac nergy innovation of external facade for existing residential ade for existing residential ade for existing residential ade for existing residential ade for existing residential ade for existing residential ade for existing residential ade for existing residential ade for existing residential ade for existing residential ade for existing residential ade for existing residential buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new buildings. It consists to taking into account both architectural and thermal aspects for new and and and old construction. construction. construction. construction. construction. With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce With the use of energy wall systems, it is possible to reduce heating heatingheating heating /cooling demand of ener /cooling demand of ener /cooling demand of ener /cooling demand of ener/cooling demand of ener /cooling demand of ener/cooling demand of ener/cooling demand of ener/cooling demand of energy consumption and gy consumption andgy consumption andgy consumption and gy consumption and gy consumption and gy consumption andgy consumption and evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy evaluate the indicators of energy performance. performance. performance. performance. performance. performance. performance. In doing In doing so, this work so, this work so, this work so, this work so, this work can contribute not only to longcan contribute not only to longcan contribute not only to long can contribute not only to longcan contribute not only to long can contribute not only to long can contribute not only to long can contribute not only to long can contribute not only to long can contribute not only to long -term economic gro term economic gro term economic groterm economic groterm economic gro term economic groterm economic groterm economic gro wth, wth, wth, but also help address pressing social, including help address pressing social, including help address pressing social, including help address pressing social, including help address pressing social, including help address pressing social, including help address pressing social, including help address pressing social, including on a wide rang on a wide rang on a wide rang on a wide rang e impact environmental impact environmental impact environmentalimpact environmental impact environmental impact environmental . We . We . We use use a dynamic simulation with structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data base a dynamic simulation with structural equation modelling to test the hypothese on data basea dynamic simulation with a structural equation modelling to test the hypothese on data base of climate of climateof climate of climate of this region. of this region. of this region. of this region. of this region. of this region. The final part The final part The final part The final part The final part The final part consists technicoconsists technico consists technico consists technicoconsists technicoconsists technicoconsists technicoconsists technico - economic approach, calculatingconomic approach, calculatingconomic approach, calculating conomic approach, calculatingconomic approach, calculatingconomic approach, calculatingconomic approach, calculating conomic approach, calculating conomic approach, calculatingconomic approach, calculatingconomic approach, calculating conomic approach, calculatingconomic approach, calculatingconomic approach, calculating conomic approach, calculating conomic approach, calculating the the the investment costs analysis, comfort and energy saving investment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy saving investment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy saving investment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy saving investment costs analysis, comfort and energy saving investment costs analysis, comfort and energy saving investment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy saving investment costs analysis, comfort and energy saving investment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy saving investment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy saving investment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy savinginvestment costs analysis, comfort and energy saving . The res The resThe res The results ults demons demons demons trate its utility in trate its utility in trate its utility in trate its utility in trate its utility in trate its utility in trate its utility in trate its utility in explaining, regarding high systems availables explaining, regarding high systems availables explaining, regarding high systems availables explaining, regarding high systems availables explaining, regarding high systems availables explaining, regarding high systems availables explaining, regarding high systems availables explaining, regarding high systems availables explaining, regarding high systems availables in innovation performance. in innovation performance. in innovation performance. in innovation performance. in innovation performance. in innovation performance. in innovation performance.in innovation performance.in innovation performance.
artical
Keywords: heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort,heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, heating/cooling, hot and dry climate, comfort, coating, investment costs.coating, investment costs. coating, investment costs. coating, investment costs. coating, investment costs.coating,